PENGARUH MODAL INTELEKTUAL, PRINSIP KONSERVATIF DALAM AKUNTANSI, DAN PRAKTIK ESG TERHADAP PERFORMA KEUANGAN PERUSAHAAN INDUSTRI DI BEI PERIODE 2023-2024 - Maximillian Corneles Parera (Jurnal Kewirausahaan Bukit Pengharapan, 2025)
This study is based on the premise that accounting conservatism, corporate intellectual capital management, and ESG (environmental, social, and governance) factors all contribute to better financial success. Financial performance here is defined as Return on Asset (ROA), and the impact of intellectual capital, ESG, and conservative accounting practices is what this study attempts to dissect. Organizations that are listed on the Indonesia Stock Exchange that fall under the industrial sector are the focus of this study, which relies on secondary data collected from financial, annual, and continuation reports. To validate the regression model, the data were first subjected to the classical assumption test in IBM SPSS 29, which checks for normality, heteroscedasticity, multicollinearity, and autocorrelation. The findings show that intellectual capital has a significant and positive effect on ROA. On the other hand, accounting conservatism is detrimental to ROA, and the results vary across ESG components. Ultimately, top brass must optimize intellectual capital management while meeting strict ESG compliance. Accounting conservatism, according to this study, should be used moderately so as not to hinder the expansion of business financial performance.